Advancement of eco-friendly slag-based high-strength geopolymer concrete - Saeeb M. AL-Tam; Amr Riad; Nader Mohammed; Ali Al-Otaibi; Osama Youssf (Journal of Materials Research and Technology)
This study investigates the production and testing of slag-based high-strength geopolymer concrete (HSGC) by incorporating various waste materials as partial substitutes for slag. The focus is on replacing slag with alternative materials such as fly ash (FA), metakaolin (MK), ceramic waste (CW), glass waste (GW), rice husk ash (RHA), and charcoal ash (CA). These alternatives are not only cheaper but also have a lower environmental impact, offering additional benefits such as reduced CO2 emissions, representing a significant step towards sustainability. Key variables, such as geopolymer binder proportions (30% and 50%), curing methods (water + steam, heat, and water), and mixing procedures, were examined. Scanning electron microscope (SEM) and energy dispersive X-ray (EDX) spectroscopy analyses were performed on selected HSGC mixes. In addition, cost and energy efficiency analyses were performed on all HSGC blends. Among the mixes tested, CA30, FA30, and FA50 showed increases in both workability (by 30%, 46%, and 79%, respectively) and compressive strength (by 39%, 28%, and 15.4%, respectively) compared to the control mix. The steam + water curing method resulted in the highest compressive strength for all mixtures, except CA30, CA50, and the control mixtures. Furthermore, CA30 and FA30 blends achieved the lowest water permeability (1.9 cm and 1.5 cm, respectively) and sorptivity (3.1 mm and 3.8 mm, respectively), compared to the control mix. Shrinkage of CA50, CW30, and GW50 mixes decreased by an average of 57%, 53%, and 79%, respectively, at all ages. Microstructure analyses revealed a dense and homogeneous matrix for these mixtures, confirming their compressive strength results and identifying them as ideal mixtures. In addition, CA50, FA50, and CW30 mixtures demonstrated higher environmental efficiency, with lower carbon emissions, reduced energy consumption, and improved cost efficiency compared to the control mix. Their values were 139, 144, and 131 MPa/t-CO2/m³, 0.573, 0.575, and 0.586 t–CO2–e/m³, and 2.98, 2.99, and 3.07 GJ/m³, respectively, with cost efficiencies of 0.13, 0.159, and 0.103 MPa-$-m³.